The ball at Versailles : a novel [compact disc, unabridged] - Steel, Danielle (Recorded Books, Llc, 2023)
In the summer of 1959, four young women receive an invitation to attend an exclusive ball in the Palace of Versailles, where American and French debutantes will be presented to international society and royalty. Though hesitant, the women attend with hopes of proving themselves and changing their lives forever. Amelia, Felicity, Caroline, and Samantha each have their own struggles and uncertainties, but the ball gives them a chance at happily ever after and to prove their worth.